Apropriação Tecnológica e Design Centrado no Aluno no Contexto de Ambientes Virtuais de Aprendizagem: aprofundando o tema pela perspectiva dos professores - Cardoso, Márcia Coelho; Silveira, Milene Selbach (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2020: Anais do XXXI Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/cbie.sbie.2020.712, 2020)
The search for improvements in the quality of education leads to interest in technological tools that support the teaching and learning activities in a student-centered design approach. The goal of this study is to explore AVAs activities and resources focusing on how they can improve technological appropriation and student-centered design. The subject is explored starting from studies on the literature, AVAs analysis, and teachers' researches highlighting the relationships between the semiotic affordance levels and technological appropriation ones as well as insights about the gap that exists between what is projected for an AVA and how it is really used.